Sistem Aplikasi Penilaian Jawaban Essay Test Calon Karyawan PT Siloam Hospitals TB Simatupang Menggunakan Algoritma Text Mining TF-IDF Berbasis Web - Agung Daniel Sipayung; Fauziah Fauziah; Nurhayati Nurhayati (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
The computer is a sophisticated technology that is widely used for now, a lot of work that used to use manual processes, has now been replaced by a computerized system, one example is the process of evaluating answers to essay tests online, the process of evaluating answers to essay tests that the authors currently use is by using the Tf-Idf text mining algorithm, which application system is a model for evaluating the essay test answers for prospective employees at PT. Siloam Hospitals TB Simatupang. The aim is to accelerate the process of evaluating essay test answers to prospective employees at PT. Siloam Hospitals TB Simatupang. In order to make the same frequency between several words in the sentence that can be used Term Frequency equation, Term Frequency is a factor that can determine word weight based on the number of word frequencies in each document, 4 sample essay questions are taken , the results can be if the prospective employee correctly solved the problem and the result or the value of the equation is 1, the value obtained by the prospective employee is 100: 4 = 25. From the results of the study that the essay test assessment system using text mining methods has worked well in the application Essay examination trials show the suitability of the assessment in the application with  the scores made by HRD with an average of 73.51%